Moral Hazards in Providing Health Services: A Review of Studies - Maryam Barati; Fereshte Azami; Beheshte Nagdi; Masoumeh Foladi; Majid Hajimaghsoudi; Salah Addin Asadi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Moral hazard is the increased likelihood of loss driven by insured behavior, which is a major the challenges faced by the insurance system. Therefore, the purpose of this study is to review the concept of moral hazard and its types, causes, consequences and control measures. Methods: This study was conducted through review, utilizing articles related to the subject in Springer's published texts, valid sites and databases such as: Google Scholar, Magiran, Medline, Springer, SID, Scopus and PubMed. The information utilized was collected from 1960-2016. Databases were searched using keywords of moral hazard in health services, causes of hazards, types of hazards in health systems, the consequences of hazards, the ways of controlling hazards, health insurance, moral hazards and health insurance. Results: The results showed that the third party (insurer) in health insurance contracts, paying a high share of treatment costs, mitigates the motivation for the behaviors of disease prevention, and prevents harm or disease, i.e.  Because the patient pays only a fraction of the cost, it has devastating consequences such as increasing insurer costs and the health system, reducing welfare, wasting resources, reducing insurance coverage, and so forth. Conclusions: Identifying various types of moral hazards, their causes and consequences in determining control strategies and reducing moral hazard and preventing undesirable outcomes are effective.